ЖАМИЯТДА ЁШЛАР ФАОЛЛИГИНИ ЮКСАЛТИРИШНИНГ МАЪНАВИЙ-АХЛОҚИЙ НЕГИЗЛАРИ (Scientific journal of the Fergana State University, 2023)
In this article the essence and content of the reforms that are consistently implemented in the society, the activity of the youth in these processes, their attitude to the national spirituality and the current scientific and theoretical issues of the spiritual and moral education of the young generation are considered.